2014
DOI: 10.1167/iovs.13-13365
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Ganglion Cell Dysfunction in Asymptomatic G11778A: Leber Hereditary Optic Neuropathy

Abstract: Declines of the PERG amplitude suggest subclinical retinal ganglion cell dysfunction in asymptomatic G11778A subjects, which is progressive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 37 publications
1
33
0
1
Order By: Relevance
“…Studies have examined the possible influence of an X-linked visual loss susceptibility locus, impaired mitochondrial respiratory chain activity, mtDNA heteroplasmy, environmental factors, and autoimmune factors [5,6]. e clinical characteristics of LHON are well documented [7][8][9][10], but fewer studies have compared visual electrophysiology with optical coherence tomography (OCT) of the retinal ganglion cell layer (GCL) and retinal nerve fiber layer (RNFL) in different stages of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have examined the possible influence of an X-linked visual loss susceptibility locus, impaired mitochondrial respiratory chain activity, mtDNA heteroplasmy, environmental factors, and autoimmune factors [5,6]. e clinical characteristics of LHON are well documented [7][8][9][10], but fewer studies have compared visual electrophysiology with optical coherence tomography (OCT) of the retinal ganglion cell layer (GCL) and retinal nerve fiber layer (RNFL) in different stages of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 It has been reported that the axons in the papillomacular bundle are the most susceptible to injury in LHON due to preferential involvement of smaller axons. 3 Recent studies have detected subclinical ganglion cell dysfunction in asymptomatic carriers using pattern electroretinogram, and structural changes of the GCC on OCT. 4,5 High-definition optical coherence tomography (OCT) has shed some light on the events occurring at the optic nerve head in LHON, including a more clear depiction of axonal swelling, which occurs before and during the time of visual loss. Furthermore, OCT clearly detects atrophy of the nerve fibre layer (RNFL) following the acute event, which in most cases is confined to the maculopapillary bundle.…”
Section: Introductionmentioning
confidence: 99%
“…Pattern electroretinographic responses originate in retinal ganglion cells. The loss and the progressive dysfunction in the macular ganglion cell layer might explain the reduced N95 component previously reported by Ziccardi et al and Guy et al in carriers . Thus the presence of macular ganglion cell layer focal thinning could be a sign that just reflects carrier status, not necessarily preceding disease development.…”
Section: Discussionmentioning
confidence: 78%
“…These abnormalities included peripapillary microangiopathy, localised swelling of the peripapillary retinal nerve fibre layer and visual fields defects . Similarly, abnormalities in colour vision and in pattern electroretinographic responses have also been described in asymptomatic carriers …”
Section: Discussionmentioning
confidence: 95%